First molecular detection of Francisella tularensis in turtle (Testudo graeca) and ticks (Hyalomma aegyptium) in Northwest of Iran - Amir Tukmechi; Abdulghaffar Ownagh; Ahmad Enferadi; Peyman Khademi (International Journal for Parasitology: Parasites and Wildlife, 2024)
Francisella tularensis, causative agent of tularemia, is a contagious zoonotic ailment. This study was aimed to molecularly detect F. tularensis in tortoise blood (n = 100) and ticks (n = 100) collected in the West Azerbaijan province, Iran suing a 16SrRNA gene of the Francisella genus through employment of the Nested-PCR technique. The identified ticks were s Hyalomma aegyptium by morphological analysis. Seven percent (with a 95% CI: 3.5%–13.75%) of animal blood samples yielded positive results for the presence of the Francisella. Meanwhile, the Francisella was identified in tick samples at a rate of fifteen percent (15%) (with a 95% CI: 9%–23%). The samples containing positive results were specifically classified as F. tularensis subsp. holarctica. The samples were taken from ticks belonging to the H. aegyptium species that were gathered in Oshnavieh, southern part of West Azerbaijan province, Iran. This research was aimed to validate the existence of F. tularensis in ticks found within the West Azerbaijan province. Consequently, it is vital to acknowledge the potential of these ticks to transmit the bacteria to both livestock and humans through tick bites in this specific area.